2022
DOI: 10.1155/2022/8639311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction and Preservation Methods on the Microbiological and Physicochemical Quality of Pentadesma butyracea Butter Produced in a Traditional Area in Benin

Abstract: P.butyracea butter, produced by different traditional methods, is often stored for further use in different types of packaging which may affect its quality. The present work aims to evaluate the effect of the production method and the type of packaging used on the physicochemical and microbiological quality of butter during storage. The extraction of Pentadesma butter was first carried out through production monitoring in three repetitions by three different butter producers according to the two most used trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The processing equipment design to move from the traditional exclusively manual scale to the mechanical scale with an optimized process would be a major innovation leading to standardized premium butter. A recent investigation has shown that the processing technology and packaging type significantly affect butter's physicochemical and microbiological properties (Badoussi et al., 2022 ). For this reason, innovation will also consider the butter package material.…”
Section: Future Prospectivesmentioning
confidence: 99%
“…The processing equipment design to move from the traditional exclusively manual scale to the mechanical scale with an optimized process would be a major innovation leading to standardized premium butter. A recent investigation has shown that the processing technology and packaging type significantly affect butter's physicochemical and microbiological properties (Badoussi et al., 2022 ). For this reason, innovation will also consider the butter package material.…”
Section: Future Prospectivesmentioning
confidence: 99%